Assessment of Respiratory Function and Need for Noninvasive Ventilation in a Cohort of Patients with Myotonic Dystrophy Type 1 Followed at One Single Expert Center. (18th June 2022) - Ferrari Aggradi, Carola R.; Falcier, Elisa; Lizio, Andrea; Pirola, Alice; Casiraghi, Jacopo; Zanolini, Alice; Carraro, Elena; Mauro, Luca; Rao, Fabrizio; Roma, Elisabetta; Iannello, Antonino; De Mattia, Elisa; et al.
Abstract : Introduction . Respiratory insufficiency is one of the main causes of death in myotonic dystrophy type 1 (DM1). Although there is general consensus that these patients have a restrictive ventilatory pattern, hypoventilation, chronic hypercapnia, and sleep disturbances, the prevalence of respiratory disease and indication for the effects of noninvasive ventilation (NIV) need to be further explored. Objectives . To describe respiratory function and need for NIV at baseline and over time in a cohort of adult patients with DM1. Methods . A total of 151 adult patients with DM1 were subjected to arterial blood gas analysis, sitting and supine forced vital capacity (FVC), peak cough expiratory flow (PCEF), nocturnal oximetry, and maximal inspiratory pressure and expiratory pressure (MIP/PEP). Results . On first assessment, 84 of 151 had normal respiratory function (median age: 38 years, median BMI: 23.9, and median disease duration: 11 years); 67 received an indication to use NIV (median age: 49 years, median BMI: 25, 8, and median disease duration: 14 years). After a median time of 3.85 years, 43 patients were lost to follow-up; 9 of 84 required NIV; only 17 of 67 with the new NIV prescription were adherent. Conclusions . We provide additional data on the natural history of respiratory function decline and treatment adherence in a relatively large cohort of well-characterized patients with DM1. A high proportion (28%) was lost to follow-up. A minority (11%) required NIV, and only 25% were treatment adherent, irrespective of specific demographics and respiratory features. Our results also confirm previous findings, showing that age, disease duration, and higher BMIs are predisposing factors for respiratory impairment.